Effects of single-dose antipurinergic therapy on behavioral and molecular alterations in the valproic acid-induced animal model of autism. (1st May 2020) - Hirsch, Mauro Mozael; Deckmann, Iohanna; Santos-Terra, Júlio; Staevie, Gabriela Zanotto; Fontes-Dutra, Mellanie; Carello-Collar, Giovanna; Körbes-Rockenbach, Marília; Brum Schwingel, Gustavo; Bauer-Negrini, Guilherme; Rabelo, Bruna; Gonçalves, Maria Carolina Bittencourt; Corrêa-Velloso, Juliana; et al.
Abstract: Autism spectrum disorder (ASD) is characterized by deficits in communication and social interaction, restricted interests, and stereotyped behavior. Environmental factors, such as prenatal exposure to valproic acid (VPA), may contribute to the increased risk of ASD. Since disturbed functioning of the purinergic signaling system has been associated with the onset of ASD and used as a potential therapeutic target for ASD in both clinical and preclinical studies, we analyzed the effects of suramin, a non-selective purinergic antagonist, on behavioral, molecular and immunological in an animal model of autism induced by prenatal exposure to VPA. Treatment with suramin (20 mg/kg, intraperitoneal) restored sociability in the three-chamber apparatus and decreased anxiety measured by elevated plus maze apparatus, but had no impact on decreased reciprocal social interactions or higher nociceptive threshold in VPA rats. Suramin treatment did not affect VPA-induced upregulation of P2X4 and P2Y2 receptor expression in the hippocampus, and P2X4 receptor expression in the medial prefrontal cortex, but normalized an increased level of interleukin 6 (IL-6). Our results suggest an important role of purinergic signaling modulation in behavioral, molecular, and immunological aberrations described in VPA model, and indicate that the purinergic signaling system might be a potential target for pharmacotherapy in preclinical studies of ASD. Highlights: ASD is characterized by deficits in sociability, sensory processing and by stereotypical behaviors. Purinergic signaling plays an important role in modulating these behaviors. Animals prenatally exposed to VPA showed purinergic-related molecular alterations. Suramin rescued ASD-like impairments in the VPA-animal model. Cytokine and purinergic signaling cross-talk are likely to modulate ASD features.